Uma investigação do abuso emocional em uma perspectiva contextualista funcional: definição, estabelecimento e consequências - Dionísio, Maria Beatriz Reis (Universidade Federal de São Carlos, 2019)
In the process of learning about emotions, the operant behavior called Arbitrarily Applied Relational Reply (RRAA), presented by the Theory of Relational Frames, is responsible for, through numerous relationships, such as the opposition, teaching us abstract relationships like that of that joy is the opposite of sadness. Although studies indicate the existence of basic emotions inherent to human beings (joy, sadness, anger, fear and disgust), and which have a large role in the regulation of organisms, culture has the function of attributing meanings or forms of control. The way in which a child, for example, will learn to control his emotions is linked to the socialization practices adopted by his caregivers. They can both contribute to the proper management of private events, as well as reinforce a distinction of superiority between emotions, which is better than another. The control strategies usually transmitted produce an individual's lack of knowledge about themselves when they encourage non-contact with certain emotions. In addition, it also generates the so-called Experiential Dodge, a way of avoiding unwanted emotions, thoughts and sensations. Violence, more specifically emotional abuse, also has a close relationship with experiential avoidance, being constantly portrayed in the literature as a driver of this type of avoidance, just as the control of emotions is. In view of these common points, the present study raised the question about the way in which we learn to control our emotions and attribute to them a valence that alters our relationship with them, being analogous to an emotional abuse. To this end, this research aimed to conduct a systematic review of the literature in order to identify the relationship between emotional control and emotional abuse.The CAPES, Scielo, LILACS, PePSIC, Web of Science databases were consulted with the keywords "emotional control" and "emotional abuse" or "psychological abuse" and their correlates in English. In total, 247 articles were found. After inserting the inclusion and exclusion criteria, the final sample totaled 8 articles. The main results showed that the articles presented, predominantly, a consequence relationship between emotional control and emotional abuse, with the first being presented as an adverse effect of the second. And they pointed out that half of the selected studies put emotional control as likely to be adequate or not, while the other four mentioned it as a negative practice. It was found, therefore, that the relationship between control and emotional abuse was mostly consequential, that there are different terms to designate the theme and, finally, it was discussed about the suppression of emotions, specifically negative, and how this control occurred along the way. story. The present study suggests that these socially employed emotions control practices are a violence towards others and oneself, as they considerably affect the emotional development of individuals and their ways of relating and expressing themselves with others.
An investigation of emotional abuse in a functional contextualist perspective: definition, establishment and consequences.
Keywords: controle emocional; Abuso emocional; Esquiva experiencial; Emotional control; Emotional abuse; Experential avoidance; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA